Tweeting in the language they understand: a peace journalism conception of political contexts and media narratives on Nigeria's Twitter ban - Auwal, Ahmad Muhammad; Ersoy, Metin (Sage Publications Ltd, 2024)
The rise of social media usage has generated global debates over efforts to address widening concerns through moderation of user practices and content that potentially undermine public safety and security. Content moderation has become a politically contested issue globally, while also attracting more attention across Africa and Nigeria in recent times. A case in point is the seven-month ban imposed on Twitter by the immediate-past government of Muhammadu Buhari, who was Nigeria's president from 2015 to 2023, following Twitter's decision to remove a tweet in which Buhari referenced the Nigerian Civil War and appeared to threaten violence against separatists in June 2021. To expand the ongoing debates about the politicization of social media use and content moderation, we conceive a peace journalism framework synthesizing the impact of political communication and media narratives on societal conflict dynamics, offering a critical reflection on the political contexts of Nigeria's Twitter ban. The theoretical lens of peace journalism was deployed to understand the implications of polarizing discourses originating from social media communication strategies of political actors. We adapt the indicators for peace versus war-oriented coverage to analyze 48 journalistic articles published across 10 English-language news outlets during the initial three-months of Nigeria's Twitter ban to assess the role that media narratives can play in mitigating or exacerbating societal tensions. Findings indicate that Buhari's Twitter-based political discourse elicits diverse perceptions of his intentions, potentially fomenting polarization, while news outlets used distinctive reporting styles that produce narratives likely to promote nonviolent responses to the ban or escalate tensions.
Keywords: Content moderation; media narratives; peace journalism; political communication; social media; Twitter ban